Effects of tobacco smoke inhalation on mast cell density and collagenation process in rat gingival tissue (Research, Society and Development, 2021)
Tobacco is one of the main risk factors for periodontal diseases, although this relationship is not fully understood. The aim of the study was to perform a histopathological evaluation of the gingiva of rats exposed to tobacco smoke inhalation. Thirty Wistar rats were grouped into three groups: rats not exposed to tobacco smoke (n=10); rats exposed to tobacco smoke inhalation for 30 days (n=10); rats exposed to tobacco smoke inhalation for 60 days (n=10). After euthanasia, plasma and gingiva were collected. In the 60-day group, a higher frequency of apoptosis, exocytosis, necrosis, hyperkeratosis, higher density of mast cells and lower percentage of collagen were observed (p>0,05). A weak, inversely proportional correlation was observed between the percentage of collagen and the density of mast cells (p>0,05). The inhalation of tobacco smoke negatively affected body mass gain besides provoking reduction in collagen percentage and increased mast cell density in the gingival tissue of rats. Thus, the findings play an important role in alerting health authorities about the deleterious effects of exposure to tobacco smoke, especially on gingival tissue.